Effects of Ultrasound Treatment and Impact Modifier on Mechanical Properties of Oil Palm Fiber Reinforced Poly (Lactic) Acid Composites - Akindoyo, John Olabode; Beg, M. D. H.; Suriati, Ghazali; Nitthiyah, Jeyaratnam (Universiti Malaysia Pahang, 2016)
In this study, composites were prepared from ultrasound treated oil palm empty fruit bunch fiber (EFB) and poly (lactic) acid (PLA) through extrusion and injection moulding. For better compatibility between fiber and matrix, the fiber was delignified through ultrasound treatment and the treated fibers were utilized for composites fabrication. Additionally, different content of impact modifier was added to study possible improvement in impact and energy absorption properties of the composites. Surface morphology and structural changes due to treatment of fibers was observed by using scanning electron microscope (SEM) and Fourier transforms infrared spectroscopy (FTIR). For composite characterization, mechanical testing such as tensile, flexural and impact were carried out. Improvements of up to 23.5%, 33.6%, 16.8% and 19.6% respectively for TS, TM, FS and FM was obtained for treated fiber composites as a result of effective delignification leading to good mechanical interlocking between the de-lignified fiber and PLA matrix. Furthermore, impact strength of poly (lactic) acid was enhanced by incorporating biostrong impact modifier, which resulted to about 38 % increase in impact strength of the resulting composite.